COVID-19 and rheumatology: A year later - B. S. Belov; A. M. Lila (Научно-практическая ревматология)
An enormous body of evidence on various aspects of the coronavirus disease 2019, COVID-19 associated with the SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus-2) has been accumulated over the past year. Meanwhile, investigated relationship between COVID-19 and rheumatic immune-mediated inflammatory diseases (IMIDs) and certain identified similarities were of paramount importance. It was shown that the incidence of COVID-19 in patients with rheumatic diseases does not significantly differ from that in general population. The risk of severe course and unfavorable COVID-19 outcomes in patients with rheumatic IMIDs is significantly associated with older age and comorbidities – as in general population, and is not aggravated by preceding use of the majority of antirheumatic drugs. Gaining better insights into pathogenesis of COVID-19 provided sound prerequisites for anti-rheumatic drugs repurposing and substantiated their use for treatment of COVID-19 infection. Under current COVID-19 pandemic circumstances, accelerated development and invention of various COVID-19 vaccines offers a great hope to curb the tide of pandemic. However, the efficacy, immunogenicity, and safety of these vaccines in patients with rheumatic IMIDs must be studied in controlled clinical trials. Generally speaking, there are still numerous blind spots in our knowledge of rheumatological aspects of such a versatile and polymorphous condition as COVID-19 infection.